Different Iron Loss Models for Electrical Steel Sheets considering Harmonic Flux Signals - Stiller, Matthias; Hahn, Ingo (IEEE International Symposium on Industrial Electronics, 2019)
The type and quality of electrical steel sheets plays an important role for the operating behavior of an electrical machine. Already during the design process of an electrical machine, the electromagnetical properties of the steel sheets and, thus, their contributions to the overall losses must be considered. Therefore, it is necessary to have a simple but also accurate method for approximating the iron losses. However, the flux density in the iron parts of an electrical machine is assumed not to be sinusoidal, whereas classical iron loss models only take sinusoidal waveforms into account. Though, several approaches try to consider also the effects of higher harmonics. This paper compares different well-known loss models for the use with arbitrary flux density waveforms.
CRIS-Team Scopus Importer:2019-08-23
Keywords: arbitrary signals; Bertotti; GSE; hysteresis losses; IEM; iGSE; iron loss models; Jordan; MSE; NSE; Steinmetz